A Multicancer Malignant Pleural Effusion Diagnostic Test Using Hexokinase 2 and Single-Cell Sequencing. (10th February 2022) - Chen, Jie; Yang, Yibin; Wang, Zhuo; Shen, Xiaohan; Zhang, Ziyuan; Wang, Chunying; Xu, Haimiao; Shi, Qihui
Abstract: Background: Malignant pleural effusion (MPE) represents advanced malignant disease with poor prognosis. To date, pleural effusion cytology remains the best test to diagnose MPE but suffers from limited diagnostic sensitivity and high variation. We report a hexokinase 2-based method (HK2-seq) as a novel diagnostic method for multicancer MPE diagnosis. Methods: HK2-seq employed HK2 as a new metabolic function-associated marker to detect disseminated tumor cells engaging increased glycolysis in pleural effusion from many cancer types. Single-cell sequencing was used to confirm the malignancy of HK2-derived high glycolytic tumor cells (hgTCs) at the single-cell level via surveying genome-wide copy number alterations (CNAs), leading to establishment of definitive MPE diagnosis. Results: In a prospective cohort study including 111 patients with pleural effusion, the HK2 test showed diagnostic sensitivity, diagnostic specificity, positive predictive value, and negative predictive value of 91% (95% CI: 80%–97%), 84% (95% CI: 68%–93%), 90% (95% CI: 79%–96%), and 86% (95% CI: 70%–95%), respectively, in MPE diagnosis across 12 different cancer types. In contrast, pleural effusion cytology exhibits an overall diagnostic sensitivity of 45%. In addition to confirming the tumor origin of hgTCs, single-cell sequencing allowed identification of prognostic or targetable CNAs in hgTCs, especially CNAs found in liquid biopsies but absent in solid biopsies. Conclusions: HK2-seq establishes definitive MPE diagnosis across many cancer types with high diagnostic performance. It has the potential to be used for multicancer detection of circulating tumor cells in blood and other types of body fluids, as well as liquid biopsy-based genomic characterization for informative diagnosis.